Digital Communication Transformation with Omni Communication Assistant (OCA): Case Study of Omnichannel and CRM Integration in Education and MSME Sector - Dimyati, Ahmad; Rusdianto, Ujang (Journal of English Language and Education, 2025)
Omni Communication Assistant (OCA) is an omnichannel-based technology developed by Telkom Indonesia to enhance digital communication across various sectors, including education and small and medium enterprises (SMEs). This study aims to analyze the implementation of OCA in digital communication, focusing on user interactivity, CRM integration, as well as challenges and optimization strategies within educational institutions and SMEs. This research employs a post-positivist paradigm with a qualitative case study approach. Data were collected through semi-structured interviews with three key informants and document analysis from various academic sources and official reports. The findings indicate that OCA improves digital communication efficiency by integrating multiple communication channels into a CRM-based system. However, challenges were identified in optimizing AI-powered chatbots, personalizing CRM services, and ensuring user readiness in adopting this technology. Therefore, strategies such as strengthening predictive AI capabilities, integrating omnichannel communication with social media, and educating users on CRM utilization are essential to enhance the effectiveness of OCA in supporting digital communication within the education and SME sectors